International politics and the search for peace - Kōsaka, Masataka, 1934-1996 (Japan Publishing Industry, 2023)
Since ancient times, humanity has put its collective wisdom toward the effort of achieving peace in the world. And yet, wars nonetheless occur over and over again. Why does the crisis of war never go away? Is it possible to realize peace in the world? First published in 1966, this introductory text on international politics by eminent Japanese political scientist Kōsaka Masataka (1934-1996) has gone through more than 50 printings in his home country and remains in print today. In this work, framed by his interest in the problems of war and of peace, Kōsaka eschewed simply schematizing or idealizing international relations, let alone--as prewar Japanese diplomats and politicians had--giving up on developing an accurate understanding of the issue by simply dismissing it as too complex to understand. Kōsaka drew on the specific cases of arms reduction, economic exchange, and international mechanisms to analyze ongoing issues that are intertwined with national interests and ideologies. By doing so, he painted a systematic portrait of the problem of peace and how to achieve it.--